COLLISION TECTONICS OF THE MEDITERRANEAN REGION: CAUSES AND CONSEQUENCES - Dilek Y. (My University, 2006)
The late Mesozoic-early Tertiary evolution of the Mediterranean region was defined by a series of collisions between Gondwana-derived continental blocks and Eurasia as the intervening ocean basins closed. The late Tertiary-Quaternary evolution of the region was controlled by the generally northward motion of Afro-Arabia and the compressional tectonics induced by the convergence between Eurasia and Afro-Arabia. Earlier collisional events caused the formation of thick orogenic crust, high-standing plateaus, and heterogeneous mantle, and resulted in slab break-offs that were collectively crucial for the onset of postcollisional collapse of the mountain belts, tectonic extension, and magmatism. The diachronous collision of Adria (Apulia), as an appendage of Africa, with Europe along its irregular margins created the Alps, the Apennines, and the Dinaride-Albanide-Hellenide mountain belt at different times and affected the formation of the Carpathians in the east. The collision of the Arabian promontory with Eurasia ca. 13 Ma facilitated the westward tectonic escape of Anatolia and caused intense deformation taken up by crustal shortening and conjugate strike-slip fault systems in a zone of ~1000 km stretching from the Bitlis-Zagros suture zone in the south to the Greater Caucasus in the north. The Anatolia plate has been rotating counterclockwise relative to Eurasia during its escape to the west and hence has been experiencing internal deformation through a combination of strikeslip and normal faulting, including metamorphic core complex formation. Subduction roll-back along the Hellenic trench has likely been the driving force for this southwest motion of Anatolia and the extensional tectonics affecting the Aegean province in the upper plate throughout the late Tertiary. The widespread alkaline volcanism both in the Aegean extensional province and in the Turkish-Iranian plateau since the late Miocene shows chemical evidence for an enriched asthenospheric mantle melt source; in both regions postcollisional slab break-off events have played a major role in providing this asthenospheric material and weakening the orogenic crust significantly. Young basins (Tyrrhenian, Aegean?) are in the process of opening above strongly arcuate subduction zones in a broadly convergent system of the Mediterranean region. The mantle response to the discrete collisional events, the geometry of colliding continental margins, and the scale of collisions strongly controlled the syn- to postcollisional tectonics and magmatism in the Mediterranean region.
Keywords: CONTINENTAL COLLISION; ESCAPE TECTONICS; LITHOSPHERIC DELAMINATION; MANTLE FLOW; MEDITERRANEAN TECTONICS; POST-COLLISIONAL MAGMATISM; SLAB BREAK-OFF; Quaternary; Miocene; Cenozoic::Quaternary; Кайнозой::Четвертичная; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен